REQUEST THAT THE AMERICAN CANCER SOCIETY BROADEN FIGHT AGAINST CANCER BY INCLUDING ENVIRONMENTAL FACTORS (Tufts Archival Research Center, 2007)
Marginalia; Letter from Michael Jacobson, Center for Science in the Public Interest, to Lane Adams, American Cancer Society. Urges ACS to be more prevention oriented and to consider prevention of exposure to carcinogens other than tobacco. Threatens national campaign highlighting limitations of ACS if ACS does not immediately establish a legislative department and reorintate towards prevention in all activities.